Smetto quando non voglio: lo smart training orientato DBT per i consumatori di cocaina - Bassini, B.; Lin, D.; Giura, G. (Mission - Open Access, 2023)
We report here the experimentation of a group of cocaine users facing two SERDP offi ces in the province of Bologna enlisted by the reference operators on a “smart” Skills training program of 10 meetings. The candidates were 8 male, with a fl uctuating relationship with substances characterized by periods of abstinence and periods of resumption of use often in conjunction with relationship diffi culties or emotional crises. All the candidates were socially integrated with a regular job, 3 of them were married with offspring and all had contacted the Relationship Service with a partner or a family member who was the fi rst to see the urgency of asking for help for the dysfunctional behavior of the relative. 4 out of 8 patients were in individual psychotherapy with the group leader who suspended individual interviews in favor of skills training for the entire duration of the group, the others benefi ted from psycho-social and educational support from a professional educator. All patients underwent the PID 5 test in the diagnostic phase and the pre-treatment phase was treated in terms of opportunity and commitment. After the 10 skills sessions, the patients will be followed up individually by taking the dbt forms and group follow-ups will be organized at 3 and 6 months. The results we report are in terms of frequency (average 66.6%), active participation and evaluation of the experience by problem consumers.